Primary Angiosarcoma of the Thyroid in an Asian Woman: A Case Report with Review of the Literature - Shih-Hsuan Huang; Shang-Chung Wu (Case Reports in Pathology)
Primary thyroid angiosarcoma is a rare malignant tumor and characterized by its prevalence in Alpine regions of Central Europe, close relation to longstanding goiter, and aggressive clinical course with dismal prognosis. We describe the case of an 83-year-old Chinese female who lives in the coastal area of Taiwan. She came to our hospital due to a progressively enlarged mass at her anterior neck. The sonography of the thyroid revealed a well-circumscribed mass in the left lobe. She underwent left hemithyroidectomy. The diagnosis of angiosarcoma of the thyroid was made and further confirmed at a different institution. To the best of our knowledge, this is the first case of primary thyroid angiosarcoma reported from Taiwan and the sixth Asian afflicted with primary thyroid angiosarcomas in the English literatures. The literature search in the PubMed database identified 58 cases who had histologically proven primary thyroid angiosarcomas. A preliminary analysis of epidemiological presentation, clinical features, immunohistochemical characters, and prognosis of primary thyroid angiosarcoma was proposed. The prognosis of this rare neoplasm is surprisingly favorable in comparison with that of its morphological similar, the anaplastic thyroid carcinoma. The use of a comprehensive panel of immunohistochemical stains, including at least two endothelial markers (especially CD31 and ERG) and PAX-8, in combination with thorough light microscopic examination may assist in the discrimination between these two tumors.